The Influence of Women's Leadership and Communication Style on Employee Engagement at PT Biofarma - Marsendah, Dea; Budiantoro, Anandha; Samryn, L.M (Journal of World Science, 2023)
This research aims to study the influence of transformational leadership style on employee engagement, mediated by the practice of subordinate communication styles with women as their direct superiors. The research method employed is quantitative in nature. Data were collected online at PT Biofarma by distributing a questionnaire comprising 40 questions. Purposive sampling was used to ensure specific conditions were met before respondents were considered eligible to fill out the questionnaire. Once all the data were collected, the study applied the SPSS method, which included correlation analysis, regression analysis, and ANOVA tables. The research results indicate that women's transformational leadership significantly impacts employee engagement through communication styles. According to the findings, there is a positive correlation between transformational leadership style and both employee engagement and communication style. Employee engagement and communication style also exhibit a positive correlation. The implications of this research underscore the need for the development of effective women leadership through training, mentoring, or specialized leadership development programs to enhance employee engagement. This study can aid in recognizing women's significant contributions in improving employee engagement, potentially leading to policies promoting recognition, promotion, or increased gender equality in organizational leadership.